The Link between HRM Practices and Performance in Malaysian SMEs - Zakaria, Nazlina; Mohd Fauzi, Waida Irani; Abdullah, Nor Azimah Chew; Yusoff, Rushami Zien (International Journal of Supply Chain Management, 2018)
This empirical study investigated HRM-performance links in Malaysian small and medium enterprises (SMEs). SMEs performance is conceptualized within a multidimensional framework consisting of four dimensions, which are satisfaction with financial performance, satisfaction with non-financial performance, performance relative to competitors and business growth. The five HRM practices adapted consisted of communication and information sharing, compensation, job design, performance appraisal, selection and training and development. The hypothesis of this study has been built on a resource based view. Field research was conducted through surveys with a total of 321 owners/managers of manufacturing SMEs, representing a response rate of 60.5%. Confirmatory factor analyses were used to analyse the quality of the scales and PLS-SEM were conducted to test the hypotheses of the study. Statistical results show certain HRM practices, namely, communication and information sharing and selection are positively related to organizational performance. Finally, this study is useful for future researchers, entrepreneurs and policy makers in realizing the importance of HRM practices towards enhancing SMEs performance.